O vinho do Porto : entre o artesanato e a agroindústria - Pereira, Gaspar Martins (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The production of Port Wine, comprising the complexity of an agricultural process involving several stages of transformation, as well as being strongly businessorientated, takes on specific characteristics determined by the natural conditions of its territory of origin, the relations between that territory and its markets and the history surrounding it. Technical evolution is, in this case, characterized by a strong connection between elements of tradition and modernity, bound by a centuries-old line of continuity, which has adapted to both slow evolutionary processes and revolutionary ruptures and innovations, especially in times of crisis, as was the case of the changes wrought by the various vine diseases during the second half of the 20th century.